2018
DOI: 10.1016/j.ijom.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Base of tongue cancer—is it tongue cancer located at the base of the tongue, or is it a type of lingual tonsil cancer? The perspective from a genomic analysis

Abstract: The aim of this study was to determine whether base of tongue (BOT) cancer is tongue cancer located at the base of the tongue or lingual tonsil cancer originating from tonsil tissue. This was a retrospective study using data from The Cancer Genome Atlas (TCGA). The genomic patterns of three primary cancers (BOT, oral tongue, and tonsil) were compared to determine their similarities and differences. Gene expression data (n=193; 26 BOT, 125 oral tongue, and 42 tonsil cases), copy number alteration data (n=142; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nine protein-coding RNAs were discovered ( Table 1 ; Supplementary Material ); HCRTR2, TSC22D1, RGPD5, TBX20, TAS1R2, LYC22D1, AC008764.4, and AC008758.5 are the specific genes of BOT carcinoma. Meanwhile, a research showed the identification of the TSC22D1 as a specific gene of BOT carcinoma ( 19 ). Hence, we finally chose TSC22D1 as a specific gene of BOT carcinoma to carry out the next phase of research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine protein-coding RNAs were discovered ( Table 1 ; Supplementary Material ); HCRTR2, TSC22D1, RGPD5, TBX20, TAS1R2, LYC22D1, AC008764.4, and AC008758.5 are the specific genes of BOT carcinoma. Meanwhile, a research showed the identification of the TSC22D1 as a specific gene of BOT carcinoma ( 19 ). Hence, we finally chose TSC22D1 as a specific gene of BOT carcinoma to carry out the next phase of research.…”
Section: Resultsmentioning
confidence: 99%
“…Tongue tonsils have crypt structures that are similar to palatine tonsils; thus, they are also the predilection sites of HPV-induced HNSCC ( 21 ). According to the results of gene data analysis of BOT carcinoma and palatine tonsillar carcinoma, BOT carcinoma has almost the same genome as tonsillar carcinoma ( 19 ); the lingual tonsil has always been a research priority on the origin of BOT carcinoma. However, it has been reported that some BOT carcinomas are deep-seated and originate from the large excretory duct of the submucosal minor salivary gland.…”
Section: Discussionmentioning
confidence: 99%